2020
DOI: 10.1177/1077801220935194
|View full text |Cite
|
Sign up to set email alerts
|

Coronavirus and Quarantine: Catalysts of Domestic Violence

Abstract: The pandemic of COVID-19 has resulted in quarantines imposed all around the world; these and other restrictions could produce an increase in domestic violence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
29
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 0 publications
4
29
0
4
Order By: Relevance
“…Many studies provided warnings about the risk of higher domestic violence rates, as a direct consequence of the restrictions established by most of the countries all over the world to manage the pandemic [ 38 , 44 , 50 , 35 , 40 , 36 , 46 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies provided warnings about the risk of higher domestic violence rates, as a direct consequence of the restrictions established by most of the countries all over the world to manage the pandemic [ 38 , 44 , 50 , 35 , 40 , 36 , 46 ].…”
Section: Resultsmentioning
confidence: 99%
“…The authors found that the prevalence of IPV was at 24.6%, with psychological violence being the most prevalent form of domestic violence. For many women and children, being confined at home with a violent partner and parent is as dangerous—and for some, more dangerous—than the COVID-19 pandemic [ 38 ].…”
Section: Resultsmentioning
confidence: 99%
“…Our review found how the dynamics of DV were explored in several studies (Anurudran et al 2020;Bouillon-Minois et al 2020;Bright et al 2020;Campbell et al 2020;Da Silva et al 2020;Dahal et al 2020;Duncan et al 2020;Ertan et al 2020;Evans et al 2020;Joseph et al 2020;Moreira et al 2020;Sacco et al 2020;Usher et al 2020). Indeed, self-isolation and social distancing can put women in constant danger by mandatory proximity with the perpetrator and isolating them from protective factors such as moments of relative freedom or access to support.…”
Section: Resultsmentioning
confidence: 94%
“…Although quarantine has been successful in slowing down the spread of the virus, poor implementation can cause additional problems in the exposed people (Pellecchia et al, 2015;Brooks et al, 2020;Buttell and Ferreira, 2020). The current quarantine due to COVID-19 has increased domestic violence, fear of people losing their jobs, reduced physical activity, altered sleep, and increased anxiety (KANTAR, 2020; How the Pandemic Could Be Messing With Your Sleep; Agren et al, 2020;Bouillon-Minois et al, 2020;Economic Commission for Latin America and the Caribbean, 2020;Mahase, 2020;Mazza et al, 2020;Spinelli et al, 2020;Thomas et al, 2020). These effects can even be more pronounced in people in developing countries where most of the population lives under the poverty line, including nations in Africa, Asia, and Latin America.…”
Section: Behavioral Implications Of Quarantine During Epidemics: a Camentioning
confidence: 99%